2013
DOI: 10.1002/bit.24917
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced degradation of haloacid by heterologous expression in related Burkholderia species

Abstract: Haloacids are environmental pollutant and can be transformed to non-toxic alkanoic acids by microbial dehalogenase. Bacterium Burkholderia species MBA4 was enriched from soil for its ability to bioremediate haloacids such as mono-chloroacetate (MCA), mono-bromoacetate (MBA), 2-mono-chloropropionate, and 2-mono-bromopropionate. MBA4 produces an inducible dehalogenase Deh4a that catalyzes the dehalogenation process. The growth of MBA4 on haloacid also relies on the presence of a haloacid-uptake system. Similar d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…Burkholderia bacteria have the ability to degrade environmental pollutants, B. xenovorans LB400 can decrease carcinogens (polychlorinated biphenyl, 2-aminophenol, Metallica) (Martıńez et al, 2007;Chirino et al, 2013;Reyes-Gallegos et al, 2016). The Burkholderia species MBA4 can enrich and bioremediate haloacids from soil (Su et al, 2013). Whether KJ-34 has the ability to decrease environmental pollutants is worthy of exploration.…”
Section: Discussionmentioning
confidence: 99%
“…Burkholderia bacteria have the ability to degrade environmental pollutants, B. xenovorans LB400 can decrease carcinogens (polychlorinated biphenyl, 2-aminophenol, Metallica) (Martıńez et al, 2007;Chirino et al, 2013;Reyes-Gallegos et al, 2016). The Burkholderia species MBA4 can enrich and bioremediate haloacids from soil (Su et al, 2013). Whether KJ-34 has the ability to decrease environmental pollutants is worthy of exploration.…”
Section: Discussionmentioning
confidence: 99%
“…These compounds have genotoxic, mutagenic, cytotoxic, and tumorigenic effects in humans (Kim et al, 2020;Long et al, 2021;. In metabolically engineered Burkholderia species, the degradation activity of haloacetic acids can be increased by 4-8 times (Su et al, 2013). The bacterial degradation of haloacetic acids was found to be affected by water distribution system conditions, including pH, phosphate, total organic carbon and residual chlorine (Behbahani et al, 2018).…”
Section: Environmental Bioremediationmentioning
confidence: 99%
“…It was also reported that MCA dehalogenase activity was found to be inducible, either in wild type of Pseudomonas sp. R1 (Ismail et al, 2008) or in its recombinant clone of Burkholderia spesies MBA4 (Su et al, 2013). Based on our result, we chose 1 mM of MCA concentration for initial optimization of inducer (IPTG) concentration.…”
Section: Growth Of E Coli Bl21 (De3)/pet-bcfd1 In Mca Containing Mediummentioning
confidence: 99%